KRITIK SANAD DAN MATAN HADITS-HADITS MASYHUR DI KALANGAN PARA DA’I: Hadits Rajab Bulan Allah, Rasulullah Saw Terlahir Sudah Dikhitan, dan Menuntut Ilmu ke Negeri China - Evalinda, Evalinda; Ghulam Nazih, Abdullah; Marwan, Andi; Wulansari, Intan; Nurani, Dewi (Asosiasi Dosen PTKIS Indonesia, 2025)
The Prophet Muhammad's Hadiths are one of the primary sources of Islamic teachings, necessitating meticulous verification to preserve their authenticity. This study examines the sanad and matan criticism of popular hadiths among preachers, focusing on three: the sanctity of the month of Rajab as